How the pigment stripes form in snapdragon (Antirrhinum majus) flowers : a study of the molecular mechanism of venation pigmentation patterning in flowers : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Molecular Biology at Massey University, Palmerston North, New Zealand - Shang, Yongjin (Massey University, 2006)
Floral stripes are a common pigmentation pattern in plants. Defining the molecular mechanisms of the striped pattern formation will aid understanding of how a gene can be differentially regulated across a population of similar cells. In the venation phenotype of Antirrhinum majus, the anthocyanin pigment is typically confined to the adaxial epidermal cells overlaying the petal veins. To explore how this pattern forms this study focused on the expression and regulation of Venosa, a Myb regulator of anthocyanin biosynthesis. Pigment complementation experiments demonstrated that the lack of a MYB factor caused the lack of pigment in the cells outside the venation pigmentation domain. An allele of Venosa was isolated and identified. It was a mutant version of functional Venosa due to the central part being replaced by a transposon. Phenotype / genotype analysis indicated that the venation pigmentation patterning was due to the functional Venosa. In situ mRNA hybridisation showed that Venosa was expressed from the xylem to the adaxial epidermis, and was controlled spatially and quantitatively by a signal associated with the petal veins. Venosa expression provided the longitudinal axis for venation pigmentation stripes, and determined the location and intensity of the pigmented cells. Because another factor required for pigmentation, a bHLH factor, is specifically expressed in epidermal cells and it provides the transverse axis. The pigmented stripes are the cross expression domain of these two kinds of factors. The transcriptional controlling property of a 2.4 kb (relative to the ATG) promoter region of the Venosa gene was analysed. The -900 bp fragment was characterised in detail using 5'-end deletion mutagenesis. A heterologous host, tobacco, was used for analysis in stable transgenics. The homologous host, Antirrhinum, was used for transient assays. The efficacy and efficiency of different reporter genes (intron-containing GUS, GFP, Venosa cDNA and genomic Venosa) and enhancement systems (transcriptional enhancer, translational enhancer, inhibitor of post transcriptional gene silencing and a two-step signaling amplification system) for the detection of low-level reporter gene expression were also tested. The strength of expression correlated to the length of the promoter fragment, and expression was detected using deletions down to -500 bp, although only weak expression was found. This expression was flower specific but not vein related in both plant hosts. No expression was detected in petals of either host with fragments shorter than -500 bp. The results suggest that the fragment from -380 bp to -900 bp positively affected Venosa expression at the transcriptional level, but might not be sufficient to define venation. A possibility is that the venation controlling property is negatively controlled at the epigenetic level, such as DNA methylation status and / or chromatin structure. The role of gibberellin and sugar in the pigment and venation patterning formation of Antirrhinum was studied. The results suggest that gibberellin is not required for pigmentation or venation patterning. Convincing evidence on the role of sugar signaling could not be obtained from the experiments, due to the difficulty in separating the impact on pigmentation from other functions of sugars in petal development. In addition, the in situ analysis detected the expression of a gene probably related to aurone biosynthesis that may be a regulatory gene of this biosynthetic pathway.
Keywords: Anthocyanin; Venosa; Gene regulation; Gene expression; Fields of Research::270000 Biological Sciences::270200 Genetics::270201 Gene expression